Analisis Tingkat Kerusakan Struktur Pada Bangunan Gedung Sekolah Dasar Negeri - Revisdah, Revisdah; Royan, Noto; Oemiati, Nurnilam; Jonizar, Jonizar (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2025)
School building is the main component of supporting teaching and learning and becomes one of the determining factors for improving the  quality of an educational institusional.The availability of facilities and infrastrctureis in important elemen as a support of  the  success of the education and teaching process in the school environment, so that proper maintenance and maintenance are needed in the use of the building, The research employed survey and interview methods. Based on the findings, five buildings were classified as lightly damaged: Building A of SDN 187, Building C of SDN 190, Building D of SDN 190, and two other Building Bs (school names not specified). One building, Building A of SDN 183, was found to be moderately damaged. Three buildings were classified as severely damaged: Building B of SDN 183, Building B of SDN 187, and a building at SDN 193. Of the total nine buildings assessed, the damage distribution was as follows: 56% lightly damaged, 11% moderately damaged, and 33% severely damaged. The total estimated repair cost for the five public elementary schools in Kalidoni District, Palembang City is Rp1,258,764,563.04 (one billion, two hundred fifty-eight million, seven hundred sixty-four thousand, five hundred sixty-three rupiah).